2022
DOI: 10.1007/s00426-022-01646-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous motor tempo over the course of a week: the role of the time of the day, chronotype, and arousal

Abstract: The spontaneous motor tempo (SMT) or internal tempo describes the natural pace of predictive and emergent movements such as walking or hand clapping. One of the main research interests in the study of the spontaneous motor tempo relates to factors affecting its pace. Previous studies suggest an influence of the circadian rhythm (i.e., 24-h cycle of the biological clock), physiological arousal changes, and potentially also musical experience. This study aimed at investigating these effects in participants‘ ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Self-paced finger-tapping rate, for instance, commonly referred to as spontaneous motor tempo (SMT) 1 , has been measured in various contextsranging from clinical 2,3 over developmental biological 4 to comparative investigations 5 . SMT has shown consistent intra-individual stability across several trials of the same task 1,6,7 (for an overview, see Ref. 8 ), yet this measure is also being discussed to be subject to contextual influences like arousal and time-of-day 6,7 , to individual influences like musicianship and age [9][10][11][12] and to interacting factors like chronotype 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-paced finger-tapping rate, for instance, commonly referred to as spontaneous motor tempo (SMT) 1 , has been measured in various contextsranging from clinical 2,3 over developmental biological 4 to comparative investigations 5 . SMT has shown consistent intra-individual stability across several trials of the same task 1,6,7 (for an overview, see Ref. 8 ), yet this measure is also being discussed to be subject to contextual influences like arousal and time-of-day 6,7 , to individual influences like musicianship and age [9][10][11][12] and to interacting factors like chronotype 7 .…”
Section: Introductionmentioning
confidence: 99%
“…SMT has shown consistent intra-individual stability across several trials of the same task 1,6,7 (for an overview, see Ref. 8 ), yet this measure is also being discussed to be subject to contextual influences like arousal and time-of-day 6,7 , to individual influences like musicianship and age [9][10][11][12] and to interacting factors like chronotype 7 . Spontaneous production or performance rate (SPR) is a measure of the more cognitively complex act of producing musical sequences 13,14 more seldomly speech sequences 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Astonishingly, although several studies have shown that motor and mental performances fluctuate across the day, following a circadian basis (∼24 h) 16 18 , the search for the optimal time-of-day for motor learning has not yet retained great attention. Daily variations were observed for maximal voluntary contractions 19 , spontaneous motor tempo 20 , speed/accuracy tradeoff of actual and mental movements 21 , handwriting 22 , and tennis service 23 . In all studies, better performances in strength or skill were consistently reported in the late afternoon than early in the morning.…”
Section: Introductionmentioning
confidence: 99%
“…In a different task type, after the introductory phase in which participants synchronise their tapping with external sounds, participants are asked to continue tapping a series without any external cues (continuation tapping task); in another type, the participant taps according to their comfortable and preferred pace, without any time pressure (spontaneous tapping task). Previous researchers have shown that spontaneous motor tempo can be observed across a broad range of activities, including walking 27 . Most of the tapping tasks listed above highly engage the participant’s working memory 1 .…”
Section: Introductionmentioning
confidence: 99%